PELAKSANAAN APLIKASI HALAMAN KAMPUNG DI DESA SUNGAI PETAI KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR TAHUN 2021 - Vadila, M. Iqbal; ', Muchid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
One of the functions of government is the service function, the government must provide the best service to meet the needs of the community in all aspects. This is being carried out by the Sungai Petai village government, where to achieve excellent public services, the Sungai Petai Village Government is presenting an Application or Mobile-based Public Service called Kampung Page. This research aims to explain the implementation of the Kampung Page application in Sungai Petai Village in 2021. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then the research location was in Sungai Petai Village, Kampar Kiri Hilir District, Kampar Regency. This research found that the implementation of the Kampung Page application in Sungai Petai village in 2021 is running quite optimally. The implementation of the public service system through the Kampung Page application in Sungai Petai village makes the public services provided more effective and efficient. The community's obstacles in using the Kampung Page application are very minimal and make the level of public trust in the Kampung Page application quite high. The reliability of using the Kampung Page application can be said to be adequate because there have been no complaints from the public regarding the speed of accessing this application. The Sungai Petai government has provided a lot of support to the community, including providing an admin chat feature, socializing the use of the Kampung Page application, providing a manual book to the community as a guide to using the Kampung Page application, and also providing kiosks at the village office for people who still lack understand how to use the Kampung Page application. However, there is still a need to improve the features of other service areas so that all service areas can be utilized optimally. Then there needs to be further outreach and training from the Sungai Petai Village government to increase knowledge and active community participation in using the Kampung Page application. Keywords: Efficiency, Level of Trust, Reliability, Support for the Community